Report of invasive tomato leaf miner, Tuta absoluta (Lepidoptera: Gelechiidae) from northern India - SHASHANK, P R; SUROSHE, SACHIN S; SINGH, P K; CHANDRASHEKAR, K; NEBAPURE, SURESH M; MESHRAM, NARESH M (The Indian Journal of Agricultural Sciences, 2016)
The tomato leaf miner or pinworn, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) is a native to South America. In October 2014 this pest was first detected infesting tomato fields in Pune, Ahmednagar, Dhule, Jalgaon, Nasik and Satara districts of Maharashtra, India Later on pest was recorded from Karnataka, Tamil Nadu, Andhra Pradesh, Telangana and Gujarat. Within two years after its first report from Maharashtra this pest is now present in New Delhi. At this point of time, it is very difficult to predict the exact route of spread within India.